SpatialLeiden: spatially aware Leiden clustering - Müller-Bötticher, Niklas; Sahay, Shashwat; Eils, Roland; Ishaque, Naveed (Genome biology, 2025)
Clustering can identify the natural structure that is inherent to measured data. For single-cell omics, clustering finds cells with similar molecular phenotype after which cell types are annotated. Leiden clustering is one of the algorithms of choice in the single-cell community. In the field of spatial omics, Leiden is often categorized as a “non-spatial” clustering method. However, we show that by integrating spatial information at various steps Leiden clustering is rendered into a computationally highly performant, spatially aware clustering method that compares well with state-of-the art spatial clustering algorithms.
Gesehen am 30.07.2025